TEACHER COMPETENCIES IN TEACHING: EDUCATION TECHNOLOGY - Yousuf S, Mohamed; Prof. Dr. Hussein Al-Abdulqader, (IJRDO- Journal of Educational Research, 2020)
Today’s education system faces the challenges to organize individuals for the information society inside which one of the preeminent points. Teachers are one of the vital resources in academic institutions. Teachers are working awfully difficult to extend the innovation framework to form it attainable for educators and learners. In order to realize the riches of information assets and instructive materials as of now realistic through the online system and elective innovation frameworks. While teaching and learning conditions, teachers are central to the question of education’s quality and performance. The student’s achievement level can be analyzed based on the teacher’s competency. For the improvement of student’s outcomes, the teachers have to face a lot of challenges while in serving mode. The education system must prepare a new genre of skilled teachers to align learner’s experiences with the changing realities of performance. In this paper, the level of competency in instructing innovation integration is portrayed.